Student Evaluation of Online Teaching Quality, Their Own Engagement and Success Expectancy in the Future Profession - Vidić, Tomislava; Klasnić, Irena; Đuranović, Marina (International Journal of Emerging Technologies in Learning (iJET), 2022)
The aim of this research was to examine students’ perceptions of online teaching, their own engagement and abilities, and their success expectancy in the future profession. 713 students attending the University of Zagreb, Croa-tia, took part in the research. The results indicate that students spend an aver-age of 6 hours studying per day. Statistically significant differences were identified in students’ perceptions of the way in which the teaching process was conducted, support provided by professors and the engagement of stu-dents in terms of the time they spend in organized and independent studying. Students who study less than 5 hours per day tend to give lower rating to the quality of the teaching process and their own engagement. Students who study more than 6 hours per day tend to give lower rating to the support pro-vided by professors. Regression analysis revealed that the perceptions of the way in which the online teaching process was organized and conducted, of the abilities, engagement and hope significantly contribute to the interpreta-tion of success expectancy in the future profession. Students’ age was not found to be a significant predictor.